Multilevel non-volatile data storage utilizing common current hysteresis of networked single walled carbon nanotubes. Issue 19 (29th April 2016) - Hwang, Ihn; Wang, Wei; Hwang, Sun Kak; Cho, Sung Hwan; Kim, Kang Lib; Jeong, Beomjin; Huh, June; Park, Cheolmin
Abstract : We developed a highly reliable non-volatile multi-level memory with an on/off current ratio greater than 10 4, retention-time 4000 s, and endurance over 100 cycles. Abstract : The characteristic source–drain current hysteresis frequently observed in field-effect transistors with networked single walled carbon-nanotube (NSWNT) channels is problematic for the reliable switching and sensing performance of devices. But the two distinct current states of the hysteresis curve at a zero gate voltage can be useful for memory applications. In this work, we demonstrate a novel non-volatile transistor memory with solution-processed NSWNTs which are suitable for multilevel data programming and reading. A polymer passivation layer with a small amount of water employed on the top of the NSWNT channel serves as an efficient gate voltage dependent charge trapping and de-trapping site. A systematic investigation evidences that the water mixed in a polymer passivation solution is critical for reliable non-volatile memory operation. The optimized device is air-stable and temperature-resistive up to 80 °C and exhibits excellent non-volatile memory performance with an on/off current ratio greater than 10 4, a switching time less than 100 ms, data retention longer than 4000 s, and write/read endurance over 100 cycles. Furthermore, the gate voltage dependent charge injection mediated by water in the passivation layer allowed for multilevel operation of our memory in which 4 distinct current states were programmed repetitively and preserved over a long time period.